Composition of the essential oils of Tanacetum armenum (DC.) Schultz Bip., T. balsamita L., T. chiliophyllum (Fisch & Mey.) Schultz Bip, var. chiliophyllum and T. haradjani (Rech. fil.) Grierson and the enantiomeric distribution of camphor and carvone - Baser, KHC; Demirci, B; Tabanca, N; Özek, T; Gören, N (WILEY, 2001)
Water-distilled essential oils from herbal parts of Tanacetum armenum (DC.) Schultz Bip., T. balsamita L.(syn. Balsamita major), I: chiliophyllum (Fisch. & Mey.) Schultz Bip. var, chiliophyllum and T. haradjani (Rech. Fil.) Grierson (endemic) (Compositae) from Turkey were analysed by GC-MS. The leaf and herb oils of T. armenum were characterized with 1.8-cineole (31% and 11%) and camphor (9% and 27%), respectively, as the main constituents. The major component characterized in the herb oil of T. balsamita was carvone (52%). Camphor (17% and 16%) was the main constituent in the oils of T. chiliophyllum var, chiliophyllum and T. haradjani, respectively. The enantiomeric distribution of carvone in the essential oil of T. balsamita and camphor in the essential oils of T, armenum, T. chiliophyllum var. chiliophyllum and T, haradjani were determined using a fused silica Lipodex E capillary column. Copyright (C) 2001 John Wiley gr Sons, Ltd.
Keywords: Tanacetum armenum (DC.) Schultz Bip.; Tanacetum balsamita L. (syn. Balsamita major); Tanacetum chiliophyllum (Fisch & Mey.) Schultz Bip chiliophyllum; Tanacetum haradjani (Rech. Fil.) Grierson; compositae; essential oil; 1,8-cineol; (1R)(+)-camphor; (1S)(-)-camphor; (S)(+)-carvone; (R)(-)-carvone; enantiomeric distribution; Chemistry; Food Science & Technology